Italian Vocal and Choral Music of the Twentieth Century as a Phenomenon of Artistic Traditions - Batovska, Olena; Grebenyuk, Natalya; Savelieva, Hanna (Journal of History Culture and Art Research, 2020)
This article is an attempt to study the leading trends of Italian vocal and choral art of the twentieth century. The main stylistic features of the musical art of the twentieth century were convincingly manifested in Italian choral music and embodied in two important tendencies in its evolution. The first tendency was focused on a conscious rethinking of traditions, the second one – on a radical technological renewal of stylistic features of musical creativity. The stimulus for updating the content, genre, and stylistic components of vocal and choral music was the “dialogue” between epochs and artistic traditions. The main results of that process were as follows: a combination of spiritual biblical themes and a modern musical language as well as stylistic innovations; the revival of the mystery genre based on texts and plots of the Holy Scriptures; the reproduction of sublime drama per musica style; the revival of the traditions of the late Renaissance madrigal and combining these traditions with new means of expression and modern techniques of composition. One of the ‘iconic’, most significant representatives of Italian musical culture of the twentieth century was Goffredo Petrassi, a composer, teacher, and conductor. G. Petrassi's choral music had an enormous effect on the development of vocal and choral music in Italy in the second half of the twentieth century. The appeal to the national heritage in Petrassi's work was associated with the revival of vocal and choral genres and manifested itself in the use of stylistic features of the late Renaissance madrigal, characteristic techniques of ancient vocal music. On the other hand, studying works of Renaissance polyphonic schools combined with a deep interest in modern experiments in the field of musical composition, allowed the composer to create an amazing phenomenon of new Italian choral music, which in composition is close to both avant-garde and neoclassical works of the first half of the twentieth century.